Integrated Management System for Equipment and Power Supply Systems in the Navigation Compartment of a Seagoing Vessel using Artificial Intelligence - Asalomia, Bogdan; Popa, Ciprian; Mihailescu, Marius Iulian; Bordianu, Adelina; Samoilescu, Gheorghe; Deliu, Florentiu; Preda, Mircea (Technium Electro, 2025)
The paper presents the importance of the modern naval transport and the integration of artificial intelligence (AI) in navigation systems. The importance of navigation equipment to meet the requirements of energy efficiency, operational safety and sustainability is emphasized. The need for energy optimization, automation and cybersecurity is underlined. The quality of electrical energy and its impact on the operation of equipment is analyzed. Concepts related to harmonics, electromagnetic compatibility (ECM), on-board electrical distribution and the characteristics of navigation equipment are presented. The optimal operation of electronic and Information Technology (IT) equipment on board is closely related to the quality of electrical energy. The key concepts regarding voltage distortions and frequency fluctuations are analyzed. The sensitivity of navigation equipment to electrical disturbances and the need for intelligent energy management are studied. The role of AI in monitoring navigation equipment is highlighted, including the description of the IT architecture, data flows and automatic signal analysis processes.